A Case Report : Thymoma Mimicking Teratoma Clinically and Radiographic Appearance - Eka Pratiwi; Djajalaksana, Susanthy; Pratiwi, Suryanti; Isharanto, Artono; Erawati, Dini; Yudhanto, Hendy (Universitaas Brawijaya, 2024)
Background: Thymoma is a rare tumor of thymic epithelial cells in anterior mediastinum. The etiology of thymoma is not known with certainty. Thymomas are difficult to distinguish from teratomas or other mediastinal tumors. Diagnosis of thymoma or teratoma is based on clinical symptoms, CXR, Thorax CT Scan, biopsy for definite diagnosis, and requires IHC examinations to be able to differentiate it from other mediastinal tumors. Case Presentation: A 62-year-old female, came with complaints of shortness of breath since 5 months when walking long distances accompanied by a dry cough for 1 week, and weight loss of 4 kgs in 10 months. Patient came from Lawang Hospital with results of AFP 1.59, B-HCG 3.8, CXR showed mediastinal mass, CT Scan Thorax showed solid mass with fat component and calcification in the right side of anterior mediastinum, suspected of a mature teratoma. Patient then underwent Tumor Excision Per Median Sternotomy by Cardiothoracic Surgeon on October 19, 2022, sampled a round tissue sized 7.5x7x6 cm with smooth surface, intact capsule likes teratoma. Discussion: PA examination was performed, with result of Germ Cell Tumor, we continued with Calretinin, CD99, SMA, S100, and Melan A IHC examinations. The results of the last IHC examination found, Type A Thymoma Cells. Patient is currently stable and recommended for radiotherapy. Conclusion: A patient with a thymoma mimicking a mature teratoma macroscopically and radiographically is an interesting case based on the results of thymoma type A from Immunohistochemistry examination but perform macroscopic likes teratoma. Keywords: Thymoma, Teratoma, Clinically, Radiographic